Analisis Protocol Routing Eigrp Pada Topologi Ring Menggunakan Simulator Cisco Packet Tracer - Rayhan Al Hayubi; Kalika Khaldan Nurshofa; Akmal Aziz; M. Taufiq Hidayatullah Syari; Didik Aribowo (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
This journal reviews the use of Cisco simulators in building and analyzing ring topology networks and the routing protocols used in them. Ring topology is one of the commonly used network topologies where all nodes are directly connected to form a circle. The routing protocol in ring topology uses Bellman Ford and Dijkstra algorithms to determine the best path. The main focus of this research is on Enhanced Interior Gateway Routing Protocol (EIGRP), a routing protocol developed from Interior Gateway Routing Protocol (IGRP). EIGRP enables fast convergence and efficiency in data transmission in the network. The research methods used are literature and simulation methods using Cisco Packet Tracer software.